Heterogeneity and subtypes of CD4+ regulatory T cells: implications for tumor therapy - Lin, Hanqing; Xu, Yuanteng; Lin, Chang (Frontiers in Immunology, 2024)
In the conventional view, CD4+ regulatory T cell (Treg) represents a subset of lymphocytes that involve the perception and negative regulation of the immune response. CD4+Treg plays an important role in the maintenance of immune homeostasis and immune tolerance. However, recent studies have revealed that CD4+Treg do not suppress the immune response in some diseases, but promote inflammatory injury or inhibit tissue remodeling, suggesting the functional heterogeneity of CD4+Treg. Their involvement in tumor pathogenesis is more complex than previously understood. This article reviews the relevant research on the heterogeneity of CD4+Treg, subtype classification, and their relationship with tumor therapy.